Physicochemical Properties, Sensory Profile, and Emotional Perception of Unpolished Organic Rice - Hadi Munarko; Muhammad A. Kurnianto; Jariyah Jariyah; Afif Arwani; Reka M. Sari (Polish Journal of Food and Nutrition Sciences)
Incorporating unpolished rice into an everyday diet improves overall health and well-being. The objective of this study was to evaluate the physicochemical properties, sensory profiles, and emotional attributes of various unpolished organic rice cultivars and their blends. Three individual samples (brown, red, and black rice) were analyzed for proximate composition, pasting properties, and texture profiles, while sensory evaluation was conducted on cooked rice for both the individual samples and three blend combinations (brown-red, brown-black, and red-black rice). A total of 70 panelists assessed the samples using rate-all-that-apply (RATA) approach, emotional sensory mapping (ESM), and hedonic perception to understand the sensory perception of products and their associations with emotional, need-state, and environmental-state attributes. The rice samples differed in their physicochemical properties, with moisture, ash, lipid, protein, carbohydrate, total energy, and energy from lipids ranging from 10.72–12.56 g/100 g, 2.88–3.57 g/100 g, 5.48–6.69 g/100 g, 9.66–12.06, 67.03–69.73 g/100 g, 365.7–376.3 kcal/100 g, and 49.3–60.2 kcal/100 g, respectively. Although the three unpolished organic rice varieties exhibited similar pasting temperatures and final viscosities, red rice showed the lowest peak viscosity and the highest hardness, which may be attributed to its higher protein content. Moreover, despite notable differences in sensory attributes such as lightness, rice color, and the roughness of appearance and texture, the unpolished organic cooked rice samples did not show significant variations in hedonic liking. A key takeaway from this study is that consumer preference for unpolished rice is not heavily influenced by emotional, need-state, or environmental-state attributes. These findings provide valuable insights for the development of technologies to improve cooked rice, particularly through improving the texture. Furthermore, future studies on the presentation of unpolished rice-based meals could provide insights into developing sensory and emotional profiles that enhance consumer acceptance.